Preparation method and application of LDH (layered double hydroxide) composite flame retardant derived from MOF (metal organic framework) with ultralow addition amount

By loading MOF on the phosphorus and nitrogen flame retardant and etching and modifying, LDH@MOF@APP composite flame retardant is solved, and the existing halogen-free flame retardant is achieved to achieve high-efficiency flame retardant effect at extremely low additive amounts.

CN119751977AActive Publication Date: 2025-04-04CHANGZHOU UNIV

Patent Information

Application Number
CN202510099509.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-04
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Existing halogen-free flame retardants require large amounts of addition to achieve the expected flame retardant effect, and the synthesis process is complex, energy consumption is high, and yield is low.

Method used

By loading the MOF base onto a phosphorus-nitrogen flame retardant and etching modification with an acid salt solution, an LDH@MOF@APP composite flame retardant with a hollow surface layered structure was formed.

Benefits of technology

It achieves flame retardant V-0 level at extremely low addition amounts, improves the flame retardant performance of plastics such as polylactic acid, simplifies the synthesis process, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of flame-retardant materials, and discloses a preparation method and application of an ultralow-additive-amount MOF-derived LDH composite flame retardant, firstly, MOF groups are loaded on a phosphorus-nitrogen flame retardant, and then etching modification is performed by using an acidic salt solution to form a double hydroxide structure with a hollow and surface layered structure, so that LDH (at) MOF (at) APP is obtained. The synthesized MOF flame retardant contains LDH components, so that the influence on the physical and mechanical properties of a high polymer material can be reduced, and meanwhile, the addition amount of the flame retardant is reduced. The MOF-derived LDH material and the flame-retardant element nitrogen are introduced into the flame retardant, so that the plastic additive with the flame-retardant function has excellent compatibility with a polylactic acid matrix. UL-94 vertical combustion V-0 grade can be passed only by an extremely low addition amount, and the limit oxygen index is greater than 26%. The preparation process is mature, convenient to operate, mild in condition and easy to popularize and apply on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardant materials, and in particular relates to an LDH composite flame retardant and a preparation method thereof and a flame retardant polymer material. Background Art

[0002] PLA is a low-cost and degradable material, but its high flammability hinders its application in practical fields. Metal-Organic Frameworks (MOFs) are a type of crystalline porous material formed by metal ions or clusters connected to organic ligands. It has the characteristics of adjustable structure, and the structure of MOF materials can be adjusted and modified to meet the flame retardant requirements. In addition, metal organic framework materials (MOFs), as organic-inorganic porous hybrid materials, have attracted much attention due to their excellent performance, especially in the field of flame retardancy. The combination of MOFs and functional polymers has become an important platform for constructing polymer-based nanocomposites, covering aspects such as controlling polymer polymerization, enhancing polymer corrosion resistance, reducing polymer dielectric constants, and constructing polymer / MOF hybrid membranes. MOFs materials overcome the shortcomings of poor compatibility between inorganic flame retardants and polymer matrices, as well as uneven molecular weight distribution and poor thermal stability of organic flame retardants, and have the potential advantages of both organic and inorganic materials. At the same time, MOFs can exhibit good flame retardant properties as flame retardants or synergists, and can improve performance in other aspects. At present, high-efficiency flame retardants for flame-retardant polylactic acid are relatively scarce on the market, and their synthesis methods are mostly hydrothermal synthesis. This method not only has a complex synthesis process, requires high temperature, high pressure and a variety of conditions, but also has a low yield. CN118515958A discloses a flame-retardant polylactic acid masterbatch obtained by melt blending and extrusion granulation of a modified aluminum diethylphosphinate flame retardant and a polylactic acid masterbatch. Although it has reached a V-0 flame retardant grade, the synthesis process is complicated and requires a large amount of different types of organic solvents, which will cause a serious burden on production costs and solvent recovery; CN202310580886.0 Preparation and application of a new flower-shaped composite flame retardant based on Co / Cu-MOF, which requires reaction in a high-pressure reactor, not only has higher energy consumption but also low yield.

[0003] The present invention uses zeolite imidazolate framework structure materials (ZIFs for short) as templates and uses etching methods to prepare halogen-free flame retardants with high-efficiency flame retardant functions. MOF precursors can prevent the accidental aggregation of layers that may occur during the conventional synthesis of LDH. Therefore, the preparation of MOF-derived LDHs can provide advanced properties and promote mass diffusion due to the formation of hierarchical channels in the layers. This may also lead to an increase in the number of metal active sites for various purposes such as energy and environmental applications. In addition, MOFs and LDHs are composed using different preparation methods, and a heterogeneous interface is introduced between MOF and LDHs to optimize the material. The resulting MOF / LDH hybrid has the important property of promoting ion and mass transport. At present, most MOF flame retardants are only added as synergists, that is, they are added in two steps while adding traditional flame retardants. The present invention loads MOF components on traditional flame retardants, which is not only more convenient and simple to add, but also utilizes the good compatibility of MOF organic components with polymer materials, reducing the deterioration of mechanical properties and transparency of plastic products. It is particularly suitable for plastics such as polylactic acid and can achieve flame retardant effects at extremely low addition amounts. Summary of the invention

[0004] In view of this, the object of the present invention is to provide an LDH-based composite flame retardant and a preparation method thereof and a flame retardant polymer material, so as to at least solve the problem that the existing halogen-free flame retardant needs to be added in large quantities to achieve the expected flame retardant effect.

[0005] The present invention solves the above technical problems by the following technical means: The MOF base is first loaded on the phosphorus-nitrogen flame retardant, and then etched and modified using an acidic salt solution to derive a double hydroxide structure with a hollow surface layered structure, namely LDH@MOF@APP.

[0006] The preparation method of LDH@MOF@APP composite flame retardant is as follows: (1) Dispersing the phosphorus-nitrogen flame retardant in a methanol solvent to obtain a mixed solution, adding the metal salt 1 to the mixed solution, stirring, and then adding dimethylimidazole thereto, reacting fully, centrifuging to obtain a solid, drying, and obtaining a MOF composite flame retardant named ZIF@APP, and heating and activating the ZIF@APP; (2) The heat-activated ZIF@APP and metal salt 2 are dissolved in a solvent respectively and then mixed and stirred thoroughly. The product is collected, washed and dried to obtain a MOF-derived composite flame retardant, which is named LDH@MOF@APP.

[0007] Furthermore, the phosphorus-nitrogen flame retardant in step (1) is one or more of ammonium polyphosphate (APP), melamine ammonium polyphosphate (MPP), 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and their derivatives.

[0008] Furthermore, metal salt 1 and metal salt 2 are any one or more of cobalt nitrate hexahydrate, nickel nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate trihydrate, and aluminum nitrate nonahydrate. Preferably, metal salt 1 is cobalt nitrate hexahydrate, and metal salt 2 is nickel nitrate hexahydrate.

[0009] Furthermore, the mass ratio of the metal salt 1, dimethylimidazole and phosphorus nitrogen flame retardant is 1:2~5:(1~5).

[0010] Further, the full reaction is: reacting at 25℃~35℃ for 8~12h, and aging for 24~48h. Heating activation is: ZIF@APP is heated at 130℃~150℃ in a vacuum oven for 2~4h and then ground; Furthermore, the mass ratio of metal salt 2 and ZIF@APP is 1:(1.5~3).

[0011] Further, sufficient stirring is mixing at a rotation speed of 800-1000 rpm for 4-8 hours.

[0012] The flame retardant application of the above-mentioned ultra-low addition MOF-derived LDH composite flame retardant in a polymer matrix.

[0013] The MOF-derived composite flame retardant (LDH@MOF@APP) prepared by the present invention introduces MOF-derived LDH materials and flame retardant element nitrogen to give the plastic additive with flame retardant function excellent compatibility with the polylactic acid matrix. Only a very low amount of addition is required to pass the UL-94 vertical combustion V-0 grade and the limiting oxygen index is greater than 27%. The preparation process of the present invention is mature, easy to operate, mild conditions, and easy to promote and apply on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a scanning electron microscope image of the raw material ammonium polyphosphate of Example 2 of Embodiment 1 of the present invention.

[0015] Figure 2 This is a scanning electron microscope image of the MOF-modified ammonium polyphosphate coated in Comparative Example 1 of the present invention.

[0016] Figure 3 This is a scanning electron microscope image of the product of Example 1 of the present invention.

[0017] Figure 4 This is a scanning electron microscope image of the product of Example 1 of the present invention.

[0018] Figure 5The XPS spectra of Example 1, Comparative Example 2 and Comparative Example 5 of the present invention are shown.

[0019] Figure 6 The XRD spectra of Example 1, Comparative Example 1, Comparative Example 5 and ammonium polyphosphate of the present invention are shown.

[0020] Figure 7 The thermogravimetric curves of pure polylactic acid of the present invention, Example 1, Comparative Example 1 and Comparative Example 3. DETAILED DESCRIPTION

[0021] Example 1: Ammonium polyphosphate (5 g) was dispersed in methanol solvent to obtain a mixed solution, Co(NO3)2·6H2O (1.44 g) was added to the mixed solution, and the mixture was stirred at 300 rpm for 30 min at room temperature. Dimethylimidazole (4.10 g) was added thereto, and the mixture was reacted at room temperature for 12 h, aged for 24 h, and centrifuged to obtain a lavender solid, which was further washed and purified with methanol, and dried in a vacuum oven at 80°C for 12 h. The solid was named ZIF67@APP.

[0022] ZIF67@APP was activated by heating at 130℃~150℃ in a vacuum oven for 2~4h and then ground. Then ZIF67@APP (5.0 g) and Ni(NO3)2·6H2O (2.25 g) were dissolved in 100 mL of methanol respectively. After the two solutions formed a uniform solution, the nickel nitrate solution was poured into the ZIF@APP solution and stirred at 300 rpm for 1.5 h at room temperature. The desired LDH@ZIF@APP was obtained. Then, the sample was washed three times with ethanol and placed in a vacuum oven at room temperature.

[0023] Example 2: Ammonium polyphosphate (5 g) was dispersed in methanol solvent to obtain a mixed solution, Zn(NO3)2·6H2O (1.56 g) was added to the mixed solution, and the mixture was stirred at 300 rpm for 30 min at room temperature. Dimethylimidazole (4.10 g) was added thereto, and the mixture was reacted at room temperature for 12 h, aged for 24 h, and centrifuged to obtain a white solid, which was further washed and purified with methanol, and dried in a vacuum oven at 80°C for 12 h. The solid was named ZIF8@APP.

[0024] ZIF8@APP was activated by heating at 130℃~150℃ in a vacuum oven for 2~4h and then ground. Then ZIF8@APP (5.0 g) and Al(NO3)2·9H2O (2.25 g) were dissolved in 100 mL of methanol respectively. After the two solutions formed a uniform solution, the nickel nitrate solution was poured into the ZIF8@APP solution and stirred at 300 rpm for 1.5 h at room temperature to obtain the desired LDH@ZIF8@APP. Then, the sample was washed three times with ethanol and placed in a vacuum oven at room temperature.

[0025] Comparative Example 1: Disperse ammonium polyphosphate (5 g) in methanol solvent to obtain a mixed solution, add Co(NO3)2·6H2O (1.44 g) to the mixed solution, stir at 300 rpm for 30 min at room temperature, add dimethylimidazole (4.10 g), react for 12 h, stand for aging for 24 h, and centrifuge to obtain a lavender solid. Further wash and purify with methanol, dry in a vacuum oven at 80 °C for 12 h, and name it ZIF67@APP.

[0026] Comparative Example 2: Co(NO3)2·6H2O (1.44 g) was completely dissolved in methanol solvent, stirred at 300 rpm for 30 min at room temperature, and then dimethylimidazole (4.10 g) was added thereto. The mixture was reacted at room temperature for 12 h, aged for 24 h, and centrifuged to obtain a lavender solid. The solid was further washed and purified with methanol, and dried in a vacuum oven at 80 °C for 12 h. The solid was named ZIF67.

[0027] ZIF67 (1 g) was activated by heating at 130°C to 150°C in a vacuum oven for 2 to 4 h, then ground and dispersed in 100 mL of methanol. Ni(NO3)2·6H2O (0.5 g) was dissolved in 100 mL of methanol. After the two solutions formed a uniform solution, the nickel nitrate solution was poured into the ZIF solution and stirred at 300 rpm for 1.5 h at room temperature. The desired LDH@ZIF was obtained. Then, the sample was washed three times with ethanol and placed in a vacuum oven at room temperature, named LDH@ZIF.

[0028] Comparative Example 3: ZIF67 (1 g) was activated by heating at 130°C to 150°C for 2 to 4 h in a vacuum oven, then ground and dispersed in 100 mL of methanol, to which Ni(NO3)2·6H2O (0.5 g) was added, reacted at room temperature for 30 min, filtered, washed, and centrifuged to obtain a light purple solid, named LDH@ZIF. LDH@ZIF and APP were mixed according to the loading ratio of Example 1, that is, the loading rate was calculated to be 9.2%, named LDH@ZIF+APP(cal.).

[0029] Comparative Example 4: Commercially available ammonium polyphosphate was added directly.

[0030] Comparative Example 5: ZIF67 as a flame retardant. The same as ZIF67 in Comparative Example 2, that is, Co(NO3)2·6H2O (1.44 g) was completely dissolved in methanol solvent, stirred at 300 rpm for 30 min at room temperature, and then dimethylimidazole (4.10 g) was added thereto, reacted for 12 h, aged for 24 h, centrifuged to obtain a lavender solid, further washed and purified with methanol, and dried in a vacuum oven at 80 °C for 12 h.

[0031] Application Example 1: The flame retardant prepared in the above embodiments and comparative examples is used in the application of preparing polylactic acid materials: different percentage weights (0.5wt%~2wt%) of the prepared flame retardant is blended and added to the polylactic acid product, the thermoplastic temperature is 180°C, the rotation speed is 50rpm, the processing time is 5min, and the flame retardant modified plastic additive modified polylactic acid material is obtained. Then, a dumbbell-shaped sample for tensile test, oxygen index test and vertical burning strip sample are prepared by injection molding machine. The tensile test is carried out according to ASTM D638-2003, the oxygen index is carried out according to ASTM D2863 standard, the UL-94 vertical burning performance is carried out according to ASTM D3801 standard, and the transparent performance is carried out according to GB / T 2410-2008 standard. The test results are shown in Table 1.

[0032] Table 1 Properties of modified polylactic acid products

[0033] As can be seen from the data in the table, it can be clearly seen from Table 1 that the plastic additive modified polylactic acid products with high-efficiency flame retardant function in Example 1 and Comparative Example 1 prepared by the present invention all show high-efficiency flame retardant properties. When the addition amount reaches 1wt% or more, the flame retardant grade is V-0. Although Comparative Example 1 has a good flame retardant effect, the mechanical properties are severely lost once it exceeds 1%. After adding 4%, the polylactic acid will directly break and even cannot be formed. Therefore, the modified products with LDH layered hydroxide structure perform better in terms of mechanical properties. Good mechanical properties have a greater promoting effect on practical applications.

[0034] Through in-depth analysis of Comparative Example 2 (LDH@ZIF) and Comparative Example 3 (LDH@ZIF + APP (cal.)), it can be seen that under the condition of extremely low addition, LDH@ZIF failed to show obvious flame retardant effect when used alone. However, when it was mixed with APP, even at an extremely low addition, the flame retardant performance of the material was significantly improved compared with that of LDH@ZIF when used alone. However, it should be pointed out that compared with the material loaded on APP in Example 1, the flame retardant effect presented in Comparative Example 3 still has a certain gap.

[0035] In sharp contrast, other material systems using coated flame retardants did not experience similar premature decomposition. This shows that during the processing of polylactic acid materials, the material system of comparative example 3 has obvious deficiencies in thermal stability, while the coated flame retardant helps to maintain the stability of the material system within the processing temperature range to a certain extent, providing more favorable conditions for the effective processing of polylactic acid materials.

[0036] Compared with pure polylactic acid, which is difficult to achieve a good flame retardant grade, adding only 1% of LDH@APP can achieve V-0 grade. Compared with the unmodified version, different percentages (0.5wt% ~2wt%) of LDH flame retardant are blended and added to polylactic acid products, and modified polylactic acid materials are prepared through a specific process. The tensile strength, elastic modulus, oxygen index, UL-94 and other properties are tested. The results show that the modified polylactic acid product has high-efficiency flame retardant properties, and the flame retardant grade can reach V-0, which has obvious advantages over other comparison ratios.

[0037] Figure 1 This is a scanning electron microscope image of unmodified commercial ammonium polyphosphate raw material. Figure 2 It is ammonium polyphosphate modified by simply coating MOF, and it is found that it grows well on the surface of ammonium polyphosphate. Due to the organic ligand structure of MOF, the compatibility with polylactic acid can be improved to a certain extent, but it is difficult to achieve a better catalytic effect due to the less exposure of active sites. Figure 3 This is the product image after etching with an acidic salt solution, which exposes more reaction sites and a good layered structure of double hydroxides, which can expose more hydrogen bonds, resulting in improved mechanical properties of the composite material. Figure 4 The results show that the etched modified MOF has a hollow structure and many layered nanosheets on the surface can have better compatibility with the plastic matrix.

[0038] Figure 5 It is the XPS image of the embodiment and the comparative example, which shows and proves the composition of the double metal layered hydroxide. In embodiment 1, it is NiCo double metal layered hydroxide. According to the electron microscope and XPS display, it can be proved that the flame retardant is successfully prepared.

[0039] In the research field of flame retardant materials, the type and content of flame retardant elements play a key role in the performance of materials. In the process of using metal salt solutions to etch ZIF67 (a metal organic framework material) to construct a specific structure, nickel salt solutions show unique advantages compared to other common metal salt solutions and are more suitable for etching ZIF67. This is because nickel salt solutions can more effectively induce ZIF67 to form a hollow structure, which is of great significance for the subsequent performance improvement of the material.

[0040] From the perspective of flame retardants, phosphorus-nitrogen synergistic flame retardants containing cobalt-nickel elements show better flame retardant properties and higher flame retardant efficiency. This is due to the synergistic effect between cobalt-nickel elements and phosphorus-nitrogen system, which can more effectively inhibit the spread of flames and reduce heat release during combustion.

[0041] In the process of applying flame retardants to plastic matrices, different layered double hydroxides (LDH) show different dispersion properties. Among them, CoNi-LDH (cobalt nickel layered double hydroxide) can be better dispersed in the plastic matrix than ZnAl-LDH (zinc aluminum layered double hydroxide). This is mainly because the ZnAl-LDH metal salt contains more crystal water. During the preparation process, these crystal waters will promote the interaction between particles, which makes it easier to cause agglomeration. Agglomerated ZnAl-LDH is not conducive to uniform dispersion in the plastic matrix, which in turn affects the overall flame retardant effect of the flame retardant. CoNi-LDH does not have this problem and can more effectively exert its flame retardant properties.

[0042] As shown in Figure 7, under specific experimental conditions, only the material system of Example 3 exhibits a relatively special thermal decomposition behavior. When the temperature reaches 230°C, the system begins to decompose prematurely. This decomposition temperature is significantly lower than the appropriate temperature range required in the processing of polylactic acid materials. This phenomenon is extremely unfavorable for the processing of polylactic acid materials.

[0043] The above situations all show that flame retardants (FR) based on metal organic frameworks (MOFs) do not have very significant advantages. However, MOF plays a key synergistic role in it. The traditional synthesis method has a complex process and high synthesis energy consumption, and it is impossible to achieve a good proportional relationship between MOF and traditional flame retardants, which leads to an increase in the amount of addition. The method proposed by the present invention can not only cleverly achieve reasonable control of the amount of MOF used by means of coating, but also use the coating of MOF to further improve the compatibility with plastics and the stability of the flame retardant.

[0044] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. An ultra-low addition MOF-derived LDH composite flame retardant, characterized in that: The MOF base is first loaded on the phosphorus-nitrogen flame retardant, and then etched and modified using an acidic salt solution to derive a double hydroxide structure with a hollow surface layered structure, namely LDH@MOF@APP.

2. The method for preparing the ultra-low addition MOF-derived LDH composite flame retardant according to claim 1, characterized in that: (1) Dispersing the phosphorus-nitrogen flame retardant in a methanol solvent to obtain a mixed solution, adding the metal salt 1 to the mixed solution, stirring, and then adding dimethylimidazole thereto, reacting fully, centrifuging to obtain a solid, and drying to obtain a MOF composite flame retardant, which is named ZIF@APP; (2) The ZIF@APP is heated and activated. The activated ZIF@APP and metal salt 2 are dissolved in solvents and mixed, stirred thoroughly, and the product is collected, washed, and dried to obtain a MOF-derived composite flame retardant named LDH@MOF@APP.

3. The method for preparing the ultra-low addition MOF-derived LDH composite flame retardant according to claim 2, characterized in that: The phosphorus-nitrogen flame retardant in step (1) is one or more of ammonium polyphosphate, melamine ammonium polyphosphate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and their derivatives.

4. The method for preparing the ultra-low addition MOF-derived LDH composite flame retardant according to claim 2, characterized in that: The metal salt 1 and the metal salt 2 are independently selected from any one or more of cobalt nitrate hexahydrate, nickel nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate trihydrate, and aluminum nitrate nonahydrate.

5. The method for preparing the ultra-low addition MOF-derived LDH composite flame retardant according to claim 2, characterized in that: Metal salt 1 is cobalt nitrate hexahydrate, and metal salt 2 is nickel nitrate hexahydrate.

6. The method for preparing the ultra-low addition MOF-derived LDH composite flame retardant according to claim 2, characterized in that: The mass ratio of the metal salt 1, dimethylimidazole and phosphorus nitrogen flame retardant is 1:4:(1-5).

7. The method for preparing the ultra-low addition MOF-derived LDH composite flame retardant according to claim 2, characterized in that: Sufficient reaction means reaction at 25℃~35℃ for 8~12h and static aging for 24~48h; heating activation means heating at 130℃~150℃ for 2~4h.

8. The method for preparing the ultra-low addition MOF-derived LDH composite flame retardant according to claim 2, characterized in that: The mass ratio of metal salt 2 and ZIF@APP is 1:(1.5~3).

9. The method for preparing the ultra-low addition MOF-derived LDH composite flame retardant according to claim 2, characterized in that: The mixture was stirred thoroughly at a speed of 800-1000 rpm for 4-8 hours.

10. The flame retardant application of the ultra-low addition MOF-derived LDH composite flame retardant according to claim 1 in a polymer matrix.

Citation Information

Patent Citations

  • Preparation method and application of cable insulating material containing composite flame retardant LDHS / ZIF-8

    CN105968492A

  • Preparation and application of novel flower-like composite flame retardant based on Co / Cu-MOF

    CN116606447A

  • Ternary nanocomposite flame retardant, flame retardant epoxy resin and method for preparing the same

    GB202212885D0

Cited By

  • Multifunctional bimetal organic framework plastic additive as well as preparation method and application thereof

    CN120554854A

  • Composite flame retardant, epoxy resin composite material and preparation method thereof

    CN122145874A